2021
DOI: 10.3390/pharmaceutics13111863
|View full text |Cite
|
Sign up to set email alerts
|

Development of Breast Cancer Spheroids to Evaluate Cytotoxic Response to an Anticancer Peptide

Abstract: Breast cancer (BC) is the most commonly diagnosed cancer in women and one of the most common causes of cancer-related deaths. Despite intense research efforts, BC treatment still remains challenging. Improved drug development strategies are needed for impactful benefit to patients. Current preclinical studies rely mostly on cell-based screenings, using two-dimensional (2D) cell monolayers that do not mimic in vivo tumors properly. Herein, we explored the development and characterization of three-dimensional (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Since the efficacy of both low molecular weight compounds and supramolecular structures differs significantly within in vitro and in vivo models, 3D spheroids are often used as an intermediate step as a more relevant tool for studying drug efficacy [21][22][23][24][25]. In particular, in spheroids, cells form tight intercellular contacts, which are often the main reason for the poor penetration of therapeutic substances into the tumor.…”
Section: D Culturementioning
confidence: 99%
“…Since the efficacy of both low molecular weight compounds and supramolecular structures differs significantly within in vitro and in vivo models, 3D spheroids are often used as an intermediate step as a more relevant tool for studying drug efficacy [21][22][23][24][25]. In particular, in spheroids, cells form tight intercellular contacts, which are often the main reason for the poor penetration of therapeutic substances into the tumor.…”
Section: D Culturementioning
confidence: 99%
“…They reported that each spheroid’s tumor microenvironment properties were different and found that the antitumor potency toward TNBC spheroids was higher than that toward HER2 + cells. Spheroids were generally more resistant to the tested peptides than monolayers …”
Section: Scaffold-free 3d Modelsmentioning
confidence: 99%
“…This demonstrates that the combination of PET tracers with spheroids and SASDM are good models for monitoring of breast cancer treatment with anticancer drugs. 35 In another study, Cavaco et al 36 developed and characterized spheroids from the most aggressive breast cancer subtypes (human-epidermal growth factor receptor-2 positive (HER2 + ) and TNBC cell lines) and also compared the efficacy of a model anticancer peptide (ACP) in both 2D (monolayer) and 3D (spheroid) cell culture models. They reported that each spheroid's tumor microenvironment properties were different and found that the antitumor potency toward TNBC spheroids was higher than that toward HER2 + cells.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides have great advantages as drugs because they have unique therapeutic properties, are usually harmless, and act on specific targets of physiological processes . Peptides that fulfill functions of regulation, modulation, and/or activation of the immune system, transport, biomarkers, and antimicrobial and anticancer activities, among others, have been described. , Recent advances in peptide therapeutics include progress from synthetic methods and in the use of naturally occurring peptides, which have intrinsic weaknesses, to a sophisticated system of drug development based on drug discovery and design, peptide synthesis, and structural modification for activity evaluation. …”
Section: Introductionmentioning
confidence: 99%